KELAYAKAN FINANSIAL DAN NILAI EKONOMI LAHAN (LAND RENT) PADA PENGGANTIAN USAHATANI KOPI MENJADI KARET DI KABUPATEN WAY KANAN PROVINSI LAMPUNG - Kaizan Kaizan; Bustanul Arifin; Hurip Santoso (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2014)
Current subsector of public coffee plantations in Lampung Province, especially at the land area  in Way Kanan District is on the wane due to farmers replacing from coffee plants to other crops plantation such as rubber. This research aims to determine the feasibility and compare the surplus value of land as well as to identify the factors that influence farmers in replacing coffee farming into rubber farming. This study was conducted in Banjit, Way Kanan district in July-August 2013 employed financial feasibility analysis methods, land rent analysis and logit analysis. The results showed that the NPV, IRR, Net B/C, Gross B/C, and payback period of two farming were still financially profitable and feasible to be developed. The feasibility valueobtained by rubber farmers still better when compared to coffee farming. Based on the land rent analysis, the surplus value of the land used as production factors of rubber farming was bigger than of coffee farming. While compared to coffee farming itself, the intercropping coffee farming had better value of feasibility and land surplus than the monoculture coffee farming. Thus, the intercropping coffee farming was more viable and economical. The greatest external factors that affected on the replacement of coffee farming into rubber farming were the period of harvest and the price; whereas, the internal factors that had real effect were farmers' income, land area, farming experience and farmer’s age. Key words: Coffee, feasibility, internal and external factors, land rent, rubbe